On the well-posedness of the Holm-Staley b-family of equations. Issue 2 (2nd April 2016) - Inci, Hasan
Abstract : In this paper we consider the Holm-Staley b -family of equations in the Sobolev spaces H s (ℝ) for s >3/2. Using a geometric approach we show that, for any value of the parameter b, the corresponding solution map, u (0)↦ u ( T ), is nowhere locally uniformly continuous.